Analisis Gaya Kepemimpinan Servant Leadership Kepala Desa Pakkanna Kecamatan Tanasitolo Kabupaten Wajo - Anggun Surya Agung; Iwan Mamminanga; Andi Supriadi (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Servant leadership style is a form of leadership that starts from an inner sincere intention to serve, prioritizing the interests of followers, collaborating with others to achieve common goals. In the context of the village head, the application of the Servant Leadership style is very relevant, but the issue that has been developing for a long time is that the role of the village head in public services is often not in accordance with community expectations. The existence of this issue makes the Servant Leadership style an important topic to discuss, one of which is by analyzing the Servant Leadership style of the Pakkanna Village Head, Tanasitolo District, Wajo Regency. The study aims to analyze how the Servant Leadership leadership style of the Pakkanna Village Head of Tanasitolo District, Wajo Regency. In addition, this research was conducted to find out the obstacles and determinants faced by the Pakkanna Village Head of Tanasitolo District, Wajo Regency in carrying out the Servant Leadership leadership style. From the results of the study, it is known that the Pakkanna Village Head has a Servant Leadership style that prioritizes service to others as the main goal of leadership. The challenges are in the form of limited resources (funds), while the determinants are commitment and supportive leadership skills and good synergy between the village head and his subordinates in carrying out public services to the Pakkanna Village community.